V. G. Ramachandra 's law of writs - RAMACHANDRAN, V. G.; C.K. Thakker; M.C Thakker; M.N. Venkatachaliah (Lucknow : Eastern Book, 2012)
This six edition of V.G. Ramachandran's great classic work "Law of Writs" has been thoroughly revised and greatly enlarged by the learned Judge and jurist, Shri C.K. Thakker, Judge, the Supreme Court of India. The expanse and coverage of the work has been greatly increased to include every possible nuance of the subject. The additional material is so extensive that the work is now published in two volumes.
Keywords: Writs India, Appellate procedure India, Appellate procedure